2011
DOI: 10.2139/ssrn.1435818
|View full text |Cite
|
Sign up to set email alerts
|

Incentive to Discriminate? An Experimental Investigation of Teacher Incentives in India

Abstract: We address the challenge of designing performance-based incentive schemes for schoolteachers. When teachers specialize in different subjects in the presence of social prejudice, performance based pay which depends on the average of student performance can cause teachers to coordinate their effort in high status students and away from low status students. Laboratory experiments conducted in India with future teachers as subjects show that performance-based pay causes teachers to decrease effort in low caste Hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a situation with strong social heterogeneity and prejudice, teachers might focus on assisting high-status students, while neglecting lower caste pupils. The experiments reveals that poorly designed incentive plans lead to such a misallocation of teacher effort, which produces unequal distribution of effort across student groups, but properly designed incentives can mitigate such behavior (Jain and Narayan 2011).…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…In a situation with strong social heterogeneity and prejudice, teachers might focus on assisting high-status students, while neglecting lower caste pupils. The experiments reveals that poorly designed incentive plans lead to such a misallocation of teacher effort, which produces unequal distribution of effort across student groups, but properly designed incentives can mitigate such behavior (Jain and Narayan 2011).…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…A laboratory experiment in India assessed teacher efforts when rewards were a function of average student test scores and revealed that poorly designed incentive plans led to the misallocation of teacher effort, which produced an unequal distribution of effort across student groups. However, properly designed incentives could mitigate such behavior (Jain and Narayan 2011). Overall, raising the quality bar still produces a positive result for craft and coping jobs ( Figure 5).…”
Section: Narrowing By Qualitymentioning
confidence: 99%
“…We think that this is reasonable, as a teacher that spent in a consistent way significantly larger amounts of time with some students than with others is likely to be challenged by parents, except for very special children (say, because they have an obvious disability). Even in countries with a history of discrimination, unequal treatment within a classroom occurs only under special circumstances (see, e.g.,Jain and Narayan (2011)).…”
mentioning
confidence: 99%